Lady Molly of Scotland Yard - Orczy, Emmuska Orczy, Baroness, 1865-1947; Cuneo, Cyrus, 1879-1916 (Salt Lake City, UT : Project Gutenberg, 2024)
"Lady Molly of Scotland Yard" by Baroness Emmuska Orczy Orczy is a collection of short stories published in 1910. This groundbreaking work features one of fiction's first female detectives, Molly Robertson-Kirk, who joins Scotland Yard's female department with a personal mission: to clear her fiancé's name. Through twelve mysteries narrated by her assistant Mary Granard, Lady Molly solves cases using superior intuition and recognition of domestic clues that escape her male colleagues, challenging the male-dominated world of early twentieth-century detective work. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lady_Molly_of_Scotland_Yard
Release date is 2024-01-01
an anonymous Project Gutenberg volunteer
Keywords: Detective and mystery stories; Police -- Great Britain -- Fiction